Priority Handling of Teurebeh Irrigation Assets, Aceh Besar District, Aceh Province - Azmeri*, Azmeri; Ar-rahman, Beryl Choliq; Jemi, Faris Zahran; Refika, Cut Dwi; Shaskia, Nina (Graduate School of Universitas Syiah Kuala, 2023)
Teurebeh Irrigation scheme is one of the promising irrigation areas in Aceh Besar District, Aceh Province. It is also one of the buffers in the agricultural sector, covering 750 hectares of agricultural area. However, the construction has shrunk over time, and the evaluation at the end of 2020 classified it as